2016
DOI: 10.1017/s0021932016000043
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Conflicts in Full- And Half-Sibling Households in the Uk

Abstract: Sibling relations are by nature ambivalent with high levels of both altruistic helping and competition. Higher relatedness is often assumed to reduce the occurrence of conflicts between siblings, but evidence of this has been scarce and mixed. Siblings typically compete over resources and parental attention, and parental constellations vary with sibship types. Since full-siblings compete over the same two biological parents, while half-siblings have only one shared biological parent and often a higher number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…Overall, both men and women were more likely to report conflicts with their own parents than with their parents-in-law. This finding is similar to recent studies of the effect of genetic relatedness on conflict proneness between siblings (Salmon and Hehman, 2015;Tanskanen et al, 2016aTanskanen et al, , 2016b,…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, both men and women were more likely to report conflicts with their own parents than with their parents-in-law. This finding is similar to recent studies of the effect of genetic relatedness on conflict proneness between siblings (Salmon and Hehman, 2015;Tanskanen et al, 2016aTanskanen et al, , 2016b,…”
Section: Discussionsupporting
confidence: 92%
“…One reason for conflicts within close family is that family members compete over resources, and the severity of kin competition may reduce or even overrun the tendencies to altruistic helping among kin (Griffin and West, 2002;Mace, 2013;Tanskanen et al, 2016aTanskanen et al, , 2016b. Inclusive fitness theory has usually been interpreted as predicting less competition and fewer conflicts with close genetic kin compared to more distant kin and non-kin (e.g., Salmon and Hehman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Structural family-level factors may also be important from an evolutionary perspective where siblings are considered as natural born competitors for limited parental resources including affection, attention or material goods (Dantchev and Wolke 2019;Tanskanen et al 2017). Children and adolescents with ASD might get priority access to these limited parental resources.…”
Section: Change In Sibling Bullying Over Timementioning
confidence: 99%
“…Nevertheless, recent evidence, intriguingly, indicates that this may not be always the case. Two recent studies among US college students (Salmon and Hehman, 2015) and British adolescents (Tanskanen et al, 2016) found full siblings to experience more conflicts than half-siblings. Sibling conflict occurrence has not, however, previously been studied among adults using large and representative data, which is the purpose of our study here.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, however, for the non-overlapping part of their kin networks, half-siblings can be predicted to exhibit no or very little competition toward each other. We call this the diluted sibling competition hypothesis (Tanskanen et al, 2016; see also Michalski and Euler, 2008).…”
Section: Introductionmentioning
confidence: 99%